The Evaluation Of Teacher Professional Education Program - Siti Habsari Pratiwi; Fasti Rola; Titin Rahmayanti Rambe; Anggili Pratama; Adi Sutopo; Abdurahman Adisaputra; Abdul Murad (PIONIR: JURNAL PENDIDIKAN, 2023)
This article uses the Provus Evaluation Model (Discrepancy Model) developed by Malcolm Provus. The current article aims to analyze whether the program is worth continuing, improving, or stopping. This model emphasizes the formulation of (1) standards, (2) performance, and (3) discrepancy in detail and measurable. The results show some general weaknesses of the teacher professional program (PPG), namely the lack of practical application of the program, where teachers focus too much on theory and not enough on practical teaching skills. Teachers may not receive adequate financial support for self-direction during the program or after they complete it. Some programs may not reflect the latest research and developments in education. Balancing teaching and professional development can be challenging, and some programs may not offer flexible scheduling and equity of training time for pre-service and in-service teachers.K